2018
DOI: 10.1007/s10867-018-9488-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AAV vector particle stability at the single-capsid level

Abstract: Virus families have evolved different strategies for genome uncoating, which are also followed by recombinant vectors. Vectors derived from adeno-associated viruses (AAV) are considered as leading delivery tools for in vivo gene transfer, and in particular gene therapy. Using a combination of atomic force microscopy (AFM), biochemical experiments, and physical modeling, we investigated here the physical properties and stability of AAV vector particles. We first compared the morphological properties of AAV vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 25 publications
(33 reference statements)
4
60
0
Order By: Relevance
“…These results are consistent with the reported amount of linear ssDNA ejected from mostly intact capsids, as described by Bernaud et al. 21 On the other hand, the accessibility of vector DNA is not an issue since all vector genomes can be released by the treatment of a lysis buffer along with proteinase K digestion. This result also suggests that the majority of vector genomes are shielded by the capsid, even after heat denaturation as high as 95°C.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with the reported amount of linear ssDNA ejected from mostly intact capsids, as described by Bernaud et al. 21 On the other hand, the accessibility of vector DNA is not an issue since all vector genomes can be released by the treatment of a lysis buffer along with proteinase K digestion. This result also suggests that the majority of vector genomes are shielded by the capsid, even after heat denaturation as high as 95°C.…”
Section: Discussionsupporting
confidence: 92%
“…The thermal stability of AAV particles has been the subject of recently published studies, which is imperative to AAV genome stability both in vitro and in vivo . 19 , 20 , 21 , 22 Studies have shown that capsid stability is notably preserved in temperatures of 4°C–55°C and a pH ranging from 5.5 to 8.5. 23 This stability is maintained in the face of interactions with human or mice serum, as well as nonorganic materials, like glass, polystyrene, polyethylene, polypropylene, and stainless steel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors affecting transduction are continually being uncovered. A recent publication combining atomic force microscopy (AFM) with biochemical experiments showed that physical properties and stability of the ssAAV particles have an influence on genome ejection pathways which in turn, can also contribute to different serotypes' transduction efficiencies [64]. At the present time we do not know whether the recently discovered AAVR receptor [65] is present in the TM, or whether its presence would add to the efficiency of the current serotypes.…”
Section: Discussionmentioning
confidence: 86%